Impact of smoking status at diagnosis on disease recurrence and death in upper tract urothelial carcinoma - Ehdaie, Behfar; Furberg, Helena; Zabor, Emily Craig; Ostroff, Jamie S.; Shariat, Shahrokh F.; Bochner, Bernard H.; Coleman, Jonathan A.; Dalbagni, Guido (BJU international, 2013)
What's known on the subject? and What does the study add? Cigarette smoking is the leading cause of urothelial carcinoma; however, the impact of smoking on outcomes after surgery for upper tract urothelial carcinoma is unknown. One study suggests that patients with a smoking history have an increased risk of recurrence in the bladder compared with never smokers but these patients did not differ with respect to time to pelvic recurrence or distant metastasis. We subdivided smokers into current and former smokers and performed multivariate analyses that showed that smoking status was not an independent predictor of recurrence when traditional prognostic factors were taken into account. In addition, competing risks analyses showed that although current smoking did not increase the risk of recurrence, it imparted a significant risk of dying compared with former and never smoking. Objective To evaluate the impact of smoking exposure on oncological outcomes in patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU). Materials and Methods Patient and disease characteristics from 288 patients with UTUC treated with RNU between 1995 and 2008 were collected from a prospectively maintained database at the Memorial Sloan‐Kettering Cancer Center. Disease recurrence was defined as distant metastases, or local failure in the operative site or regional nodes. Factors associated with recurrence and death were determined. Results The prevalence of current, former and never smoking at diagnosis was 19.1%, 55.2%, and 25.7%, respectively. 71.0% of patients reported a ≥20 pack‐year smoking history. With a median follow‐up of 4.02 years, disease recurrence occurred in 27% (n = 79) of patients and 41% (n = 117) died during follow‐up. While age at diagnosis, American Society of Anesthesiologists score, advanced stage, nodal involvement and high grade adversely affected recurrence‐free survival, smoking status was not associated with risk of recurrence or death in multivariate analysis (P = 0.60). Multivariate competing risks regression showed that current smokers faced a significantly higher risk of death than never smokers (hazard ratio 3.64, 95% confidence interval 1.59–8.34). Conclusions While smoking status at diagnosis and cumulative smoking exposure were not associated with UTUC recurrence, our findings highlight the substantial risk of death in patients with UTUC who are active smokers. Treatment plans to promote smoking cessation are recommended for these patients.